A changed post‐flood management strategy enables the culture‐based fishery of the Liangzi Lake, Yangtze River Basin, China, to remain economically and environmentally viable. (2nd September 2019) - Wang, Qidong; Li, Zhongjie; Lin, Mingli; Ye, Shaowe; Li, Wei; Guo, Chuanbo; Huang, Geng; Yuan, Jing; Liu, Jiashou; De Silva, Sena S.
Abstract: The culture‐based fishery of Liangzi Lake, Yangtze River Basin, established in 1992, yielded 2, 652 t/year (±167) between 2005 and 2015, dominated by stocked carps [ Hypophthalmichthys molitrix (Val.) and Hypophthalmichthys nobilis (Richardson)] and mitten crab Eriocheir sinensis (Milne Edwards), accounting for 53% and 23% of the production and 20% and 52% in value, respectively. The lake had a macrophyte cover dominated by Vallisneria natans (Lour.) Hara with a cumulative biomass of 10, 647 g/m 2 that disappeared after a major flood in 2010 and changed its ecology. Management changes in stocking strategies introduced in the post‐flood period enabled the culture‐based fishery to maintain viability and sustainability to combat the major ecological change in the lake. The stocked species contributed significantly to nutrient removal of 24.71 ± 5.12 t/yr and 6.29 ± 0.87 t/yr of total nitrogen and total phosphorus, respectively.